The design of the multipurpose swing / Iqbal Mohamad Sohod … [et al.] - Sohod, Iqbal Mohamad; Za' bar, Mohd Arif; Mohamed, Ahmad Zaki; Hassim, Abu Sufian (2009)
This study will discuss about furniture design. This design consist of multipurpose function that we can save the budget due to its functions. This study is also to find as much information about the design of swing. Beside that, we also want to know the advantages of using this multipurpose swing. Furthermore are to know and to provide knowledge of wood species and suitability to produce furniture. The impression of the uses wood not only because of it properties but wood has the high aesthetics value to make the furniture look beautiful.